Design Evaluations of Aerosol Suction Machine for Dental Treatment Practices in COVID-19 Era - Fitrian Imaduddin; Seraf Steva Oryzanandi; Budi Santoso; Raymundus Lulus Lambang Govinda Hidayat (Mekanika: Majalah Ilmiah Mekanika, 2021)
This paper aims to demonstrate the evaluation process to select the Aerosol Suction Machine (ASM) design to be implemented in a dental treatment practice to prevent the spread of Coronavirus Disease (COVID-19). There are two designs evaluated, the movable ASM and the fixed mounting ASM. The evaluation process involved four criteria: flexibility, safety level, manufacturability, and maintenance. The evaluation is conducted based on a specific requirement of a small dental clinic located in Surakarta, Indonesia. The evaluation results show that the fixed mounting is more suitable for implementation in a small dental clinic with many natural ventilation openings.